Metode tafsir kontemporer Abdullah Saeed - Ummah, Sun Choirol (Universitas Negeri Yogyakarta, 2018)
The Qur'an as an open book does not close the ongoing interpretation in accordance with the times, situations and conditions. This is important so that the Qur'an does not experience stagnation of meaning. The problem arises when some Muslim scholars do not have the courage to develop the meaning and interpretation of the Qur'an which is considered sinful and fears of changing the Qur'anic text. In other spaces, it turns out that the meaning of the Qur'an with the classical approach will be considered rigid, and untouchable. Abdullah Saeed captures how the efforts to interpret the Qur'an must continue and adapt to the times. Departing from the courage of the companions of the Prophet Muhammad in interpreting the verses about the law, it turns out that the law must be arrested in accordance with its laws, not just enforcing its laws. In line with Saeed, some scientists interpret the method and approach of the Qur'an to carry out concept renewals, from textual, semi-textual, contextual, and contextual progressive. Saeed defined himself to the interpreter with a contextual progressive approach. That is, the interpretive approach considers legal-legal ethics and value hierarchy. The reader should carry out a continuous process of interpretation of the text and be adapted to the socio-historical context.Alquran sebagai kitab terbuka tidak menutup interpretasi yang berkelanjutan sesuai dengan perkembangan zaman, situasi dan kondisi. Hal ini penting agar Alquran tidak mengalami kemandegan makna. Permasalahan muncul ketika sebagian sarjana Muslim tidak memiliki keberanian untuk mengembangkan makna dan penafsiran Alquran yang dinilai berdosa dan kekhawatiran merubah teks Alquran. Di ruang lainnya ternyata pemaknaan Alquran dengan pendekatan klasik akan dianggap kaku, rigit, dan tak tersentuh.Abdullah Saeed menangkap betapa upaya pemaknaan Alquran harus terus dilanjutkan dan disesuaikan dengan perkembangan zaman. Berangkat dari keberanian para sahabat Nabi Muhammad dalam menafsirkan ayat-ayat tentang hukum, ternyata hukum harus ditangkap sesuai dengan etis-hukumnya, tidak justru menegakkan legal-hukumnya. Senada dengan Saeed beberapa ilmuwan metode dan pendekatan tafsir Alquran mengadakan pembaruan-pembaruan konsepnya, dari tekstualis, semi-tekstualis, kontekstualis, dan progesif kontekstualis. Saeed mendefinisikan dirinya pada penafsir dengan pendekatan progesif kontekstualis. Artinya, pendekatan tafsirnya mempertimbangkan etis-legal teks dan hirarki nilai. Pembaca seharusnya melakukan proses interpretasi secara berkesinambungan (a continous process) terhadap teks dan disesuaikan dengan socio-historical context-nya.